Advanced CRISPR/Cas-based genome editing tools for microbial biofuels production: A review. (April 2020) - Shanmugam, Sabarathinam; Ngo, Huu-Hao; Wu, Yi-Rui
Abstract: With rapid progress in the fields of synthetic biology and metabolic engineering, there are possible applications to generate a wide range of advanced biofuels with maximized yield and productivity to achieve a more sustainable bioprocess with reduced carbon footprints. Among the diverse molecular biology tools, clustered regularly interspaced short palindromic repeats-CRISPR-associated proteins (CRISPR-Cas) technology stands out with potential targeted genome editing, exhibiting a more precise and accurate gene knock-out and knock-in system better than its predecessors, for example zinc finger nucleases (ZFN) and transcription activator-like effector nucleases (TALEN). There are reports involved in the advanced microbial genome engineering tools for the biofuels production; however, there is lack of a comprehensive review about the CRISPR-Cas based-techniques in improved biofuel production along with the strategies to reduce the off-target effect that ensures the success and safety of this method. Therefore, in this review we attempt to systematically comment on the mechanism of CRISPR-Cas and its application to microbial biofuels production. This includes bioethanol, biobutanol as well as other hydrocarbons that sequentially follow various suggestions on enhancing the efficiency of targeting genes. The role of inducible on/off genetic circuits in response to environmental stimuli in the regulation of targeted genome editing (TGE) by minimizing metabolic burden and maximizing fermentation efficiency is also discussed. The relevant stringent regulatory demands to ensure minimal off-target cleavage with maximum efficiency coupled with complete biosafety of this technology are considered. It can be concluded that the recent development of CRISPR-Cas technology should open a new avenue in creating microbial biorefineries for potentially enhanced biofuel production. Highlights: This review focuses on CRISPR-Cas technology in improved biofuels production. Utilization of diverse CRISPR-Cas machinery for biofuels production was reviewed. Enhancing the targeting gene efficiency by CRISPR genetic circuits were discussed. Perspectives of methods for reducing off-target effects were summarized.